1996
DOI: 10.1063/1.117570
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical detection of magnetic resonance by angular momentum absorption

Abstract: Observations of electron paramagnetic resonance by means of the angular momentum absorbed by a small sample are reported. The method is based on the detection of the torque induced in a microcantilever, like the ones employed in atomic force microscopy, integral with the sample. The results obtained with this experimental scheme are compared with the ones of the Sidles–Rugar method exploiting a force detection of the magnetic resonance in presence of strong magnetic field gradients. In particular, the signal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…The high detection sensitivity of resonant nanomechanical torque sensors has allowed for minimally-invasive observations of magnetostatic interactions and hysteresis in a variety of magnetic materials including thin films [15], mesoscale confined geometries that are deposited [16] or epitaxially grown [17], and small aggregates of nanoparticles [18]. Going beyond the static limit, nanomechanical torque magnetometry has been extended to timescales allowing for detection of slow thermally-activated dynamics [12], AC susceptibility [17], and magnetic resonance [19,20].This powerful technique relies upon detection of the deflection of a mechanical element by angular momentum transfer originating from magnetic torques τ = µ 0 m×H, generated as the magnetic moments in the system, m, experience an orthogonally-directed component of the applied magnetic field, H. So far, improvements to torque magnetometers have been driven primarily by enhancements to the response of nanomechanical resonators resulting from their low mass and high mechanical quality factor (Q m ). Readout of magnetically driven motion has involved detection through free-space optical interferometric methods with very low optical quality factor (Q o ≈ 1) Fabry-Perot cavities formed between the nanomechanical resonator its supporting substrate [16].…”
mentioning
confidence: 99%
“…The high detection sensitivity of resonant nanomechanical torque sensors has allowed for minimally-invasive observations of magnetostatic interactions and hysteresis in a variety of magnetic materials including thin films [15], mesoscale confined geometries that are deposited [16] or epitaxially grown [17], and small aggregates of nanoparticles [18]. Going beyond the static limit, nanomechanical torque magnetometry has been extended to timescales allowing for detection of slow thermally-activated dynamics [12], AC susceptibility [17], and magnetic resonance [19,20].This powerful technique relies upon detection of the deflection of a mechanical element by angular momentum transfer originating from magnetic torques τ = µ 0 m×H, generated as the magnetic moments in the system, m, experience an orthogonally-directed component of the applied magnetic field, H. So far, improvements to torque magnetometers have been driven primarily by enhancements to the response of nanomechanical resonators resulting from their low mass and high mechanical quality factor (Q m ). Readout of magnetically driven motion has involved detection through free-space optical interferometric methods with very low optical quality factor (Q o ≈ 1) Fabry-Perot cavities formed between the nanomechanical resonator its supporting substrate [16].…”
mentioning
confidence: 99%
“…In addition to the forces and torques on the sample that result in the predicted experimental signatures of atomic resolution magnetic resonance diffraction, additional measurement methods may achieve predicted spectral features. Several nonimaging cantilever-type experiments have been reported that rely on the direct transfer of angular momentum 36,37 and energy 38,39 to the spin population in magnetic resonance. Such experiments have demonstrated similar sensitivity to the initial demonstrations of imagingtype, cantilever-detected magnetic resonance, and therefore also represent possible routes to atomic resolution magnetic resonance diffraction demonstration.…”
Section: ͑21͒mentioning
confidence: 99%
“…It should be noted that the high Q values often reduce by up to two orders of magnitude due to the interaction with the strong, external magnetic field (required for the alignment of the spins) during the actual MRFM experiments. The majority of the reported designs excited normal vibration mode in the cantilever, while few publications describe also the usage of torsional vibration [225,226].…”
Section: Instrumentationmentioning
confidence: 99%